FAKTOR-FAKTOR YANG MEMPENGARUHI TOKSISITAS BAHAN PENCEMAR TERHADAP ORGANISME PERAIRAN - Triyoni Purbonegoro (OSEANA, 2019)
FACTORS THAT AFFECTING THE TOXICITY OF POLLUTANTS TO AQUATIC ORGANISMS. There are a large number of pollutants in aquatic environment with various characteristics and factors that can modify and affect the toxicity of pollutants in this environment. The major factors affecting pollutant toxicity include physicochemical properties of pollutants, mode of exposure, time, environmental factors, and biological factors. Moreover, organisms in an aquatic ecosystem are seldom exposed to only single pollutant, and most cases the stress of pollution on aquatic ecosystems is related to the interaction and combined effects of many chemicals. The combined effects may be synergistic or antagonistic, depending on the pollutants and the physiological condition of the organism involved.